Borderline Personality Features in Students: The Predicting Role of Traumatic Experiences and Aggressive Traits - Seyedeh Fatemeh Sajjadi; Habibe Riyahi; Sanaz Behbuei (Shiraz University of Medical Sciences, 2017)
Background: Borderline personality (BP) is a serious mental condition in clinical practice which is marked by aggression and is shown to be affected by traumatic life events. Objectives: This study aimed to determine the relationship between early trauma and aggressive traits as predictive factors of borderline personality features (BPF) in high school students. Methods: Three hundred and eleven students with mean age of 16.66 were recruited via multi stage random sampling. All the participants were asked to complete borderline personality features scale for children, early trauma inventory, and buss-perry aggression questionnaire. Analyzing data was done using canonical correlation. Results: The results indicated that BPF is predicted by early trauma and aggression traits. Conclusions: In general, the findings showed that early trauma, physical aggression, verbal aggression, anger, and hostility can predict BPF and explain a considerable variance of survival index.